Effects of intramuscular alfaxalone and dexmedetomidine alone and combined on ocular, electroretinographic, and cardiorespiratory parameters in normal cats - Guo, Yizhe; Mao, Sichao; Zhou, Zhenlei (Frontiers in Veterinary Science, 2024)
Background This study aimed to determine the effects of intramuscular (IM) administration of alfaxalone with or without dexmedetomidine on short electroretinography (ERG), ocular parameters and cardiorespiratory in healthy cats. Methods Eight healthy female spayed cats were treated with three sedation protocols: IM administration of 5 μg/kg dexmedetomidine (DEX), 5 mg/kg alfaxalone (ALF), and 5 μg/kg dexmedetomidine plus 5 mg/kg alfaxalone (DEX + ALF). The washout period after each treatment was 2 weeks. Physiological parameters, time metrics, intraocular pressure (IOP), Schirmer tear test 1 (STT-1) and a short ERG protocol were recorded. For age data, weight data, time metrics and ERG data, one-way ANOVA with Bonferroni posterior comparisons were performed. For physiological parameters, IOP and STT-1 data, two-way repeated measures ANOVA with Bonferroni posterior comparisons were performed. Statistical significance was set at a p-value <0.05. Results IOPs were increased in all three groups compared to baseline and showed no significant differences among three groups at any time point. STT-1 values were decreased significantly during the process. Significant differences were noticed between a-wave amplitude in the dark-adapted response between DEX and ALF, and a-wave amplitude in light-adapted response between ALF and DEX + ALF. Conclusion This study demonstrates the feasibility of three sedation protocols for short ERG recording in cats. All these treatments resulted in increased IOP values and reduced STT-1 values. But baseline data of ERG was not obtained as a blank control in cats.